High-quality semiconductor fibres via mechanical design - Wang, Zhixun (2024)
Recent breakthroughs in fibre technology have enabled the assembly of functional materials with intimate interfaces into a single fibre with specific geometries1-11, delivering diverse functionalities over a large area, for example, serving as sensors, actuators, energy harvesting and storage, display, and healthcare apparatus12-17. As semiconductors are the critical component that governs device performance, the selection, control and engineering of semiconductors inside fibres are the key pathways to enabling high-performance functional fibres. However, owing to stress development and capillary instability in the high-yield fibre thermal drawing, both cracks and deformations in the semiconductor cores considerably affect the performance of these fibres. Here we report a mechanical design to achieve ultralong, fracture-free and perturbation-free semiconductor fibres, guided by a study on stress development and capillary instability at three stages of the fibre formation: the viscous flow, the core crystallization and the subsequent cooling stage. Then, the exposed semiconductor wires can be integrated into a single flexible fibre with well-defined interfaces with metal electrodes, thereby achieving optoelectronic fibres and large-scale optoelectronic fabrics. This work provides fundamental insights into extreme mechanics and fluid dynamics with geometries that are inaccessible in traditional platforms, essentially addressing the increasing demand for flexible and wearable optoelectronics.